2020
DOI: 10.20546/ijcmas.2020.907.204
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Extent of Technological Gap in Adoption of Scientific Practices of Tea Cultivation by Small Tea Growers of Assam

Abstract: The study was conducted in Sonitpur and Biswanath districts of Assam with 100 Small Tea Growers to identify the factors influencing the extent of technological gap in adoption of scientific practices of tea cultivation by small tea growers. An analysis of the small tea production system is the quite important to the subject of development of the small tea growers as well as improving the productivity tea on small holdings. It was found that majority of the respondents (71.00%) had medium overall technological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similarly majority of farmers (61%) knew about the impact of global warming on sea level and 86% respondents had knowledge about the impact of climate change in arid ecosystem [1]. A study conducted on knowledge of small tea growers regarding scientific tea cultivation practices revealed that majority of respondents (72.00%) had medium level of knowledge, whereas 15.00 per cent and 13.00 per cent of growers had low and high level of knowledge about scientific tea cultivation practices, respectively [2]. Knowledge was considered to be one of the important components of behaviour playing an important role in the covert and overt behaviour of an individual [3].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly majority of farmers (61%) knew about the impact of global warming on sea level and 86% respondents had knowledge about the impact of climate change in arid ecosystem [1]. A study conducted on knowledge of small tea growers regarding scientific tea cultivation practices revealed that majority of respondents (72.00%) had medium level of knowledge, whereas 15.00 per cent and 13.00 per cent of growers had low and high level of knowledge about scientific tea cultivation practices, respectively [2]. Knowledge was considered to be one of the important components of behaviour playing an important role in the covert and overt behaviour of an individual [3].…”
Section: Introductionmentioning
confidence: 99%